Immune-related adverse events are clinical biomarkers to predict favorable outcomes in advanced renal cell carcinoma treated with nivolumab plus ipilimumab. (10th February 2022) - Ueda, Kosuke; Suekane, Shigetaka; Kurose, Hirofumi; Ito, Naoki; Ogasawara, Naoyuki; Hiroshige, Tasuku; Chikui, Katsuaki; Ejima, Kazuhisa; Uemura, Keiichiro; Nakiri, Makoto; Nishihara, Kiyoaki; Igawa, Tsukasa
Abstract: Background: Immune checkpoint inhibitors cause various immune-related adverse events. The present study examined the association between the incidence of immune-related adverse events and survival outcomes in patients treated with nivolumab plus ipilimumab for patients with advanced renal cell carcinoma. In addition, we compared the effect of adverse event profiles on survival for patients receiving nivolumab plus ipilimumab. Methods: A total of 35 patients with advanced renal cell carcinoma who were treated with nivolumab plus ipilimumab from August 2018 to August 2021 were retrospectively reviewed and analyzed. Cox proportional hazards models were used for univariate and multivariate analyses, and hazard ratio and 95% confidence intervals were calculated. Results: Of the 35 patients, 22 (62.9%) experienced immune-related adverse events. The median progression-free survival ( P = 0.0012) and overall survival ( P = 0.0147) were significantly longer in patients with immune-related adverse events than in those without immune-related adverse events. Multivariate analysis showed that the incidence of immune-related adverse events was an independent factor for progression-free survival (hazard ratio = 4.940, 95% confidence interval: 1.558–15.664, P = 0.0067). Skin reaction was a positive predictive immune-related adverse events for progression-free survival (hazard ratio = 9.322, 95% confidence interval: 1.954–44.475, P = 0.0051). Conclusion: Patients with advanced renal cell carcinoma with immune-related adverse events had superior clinical outcomes of nivolumab plus ipilimumab treatment than those without immune-related adverse events. Skin immune-related adverse events may be effective biomarkers in patients with advanced renal cell carcinoma treated with nivolumab plus ipilimumab. Abstract : Advanced renal cell carcinoma patients with immune-related adverse events treated with nivolumab plus ipilimumab had superior clinical outcomes. Skin immune-related adverse events may be effective biomarkers for nivolumab plus ipilimumab.